Posttraumatic Spinal Cord Injury without Radiographic Abnormality - Kivanc Atesok; Nobuhiro Tanaka; Andrew O’Brien; Yohan Robinson; Dachling Pang; Donald Deinlein; Sakthivel Rajaram Manoharan; Jason Pittman; Steven Theiss (Advances in Orthopedics)
“Spinal Cord Injury without Radiographic Abnormality” (SCIWORA) is a term that denotes objective clinical signs of posttraumatic spinal cord injury without evidence of fracture or malalignment on plain radiographs and computed tomography (CT) of the spine. SCIWORA is most commonly seen in children with a predilection for the cervical spinal cord due to the increased mobility of the cervical spine, the inherent ligamentous laxity, and the large head-to-body ratio during childhood. However, SCIWORA can also be seen in adults and, in rare cases, the thoracolumbar spinal cord can be affected too. Magnetic resonance imaging (MRI) has become a valuable diagnostic tool in patients with SCIWORA because of its superior ability to identify soft tissue lesions such as cord edema, hematomas and transections, and discoligamentous injuries that may not be visualized in plain radiographs and CT. The mainstay of treatment in patients with SCIWORA is nonoperative management including steroid therapy, immobilization, and avoidance of activities that may increase the risk of exacerbation or recurrent injury. Although the role of operative treatment in SCIWORA can be controversial, surgical alternatives such as decompression and fusion should be considered in selected patients with clinical and MRI evidence of persistent spinal cord compression and instability.